PENERAPAN METODE TAHFIDZ AL-QUR’AN DI UNIT KREATIVITAS MAHASISWA JAM’IYYATUL QURRA’ WAL-HUFFAZH UNIVERSITAS ISLAM MALANG - Rahmad Toullah Tawainella; Rosichin Mansur; Siti Masyruhah (VICRATINA, 2022)
This study aims to describe the application of the Qur'an tahfidz method in UKM JQH UNISMA. In this study, the position of the researcher was to observe the conditions of the application of the Qur'an tahfidz method on UNISMA students who took part in the tahfidz program. Data was collected through three methods: Interview, Documentation, and Observation. The results of this study indicate that, 1) planning tahfidzul in UKM JQH UNISMA there are 4 stages, namely preparation, notification, implementation, and evaluation. 2) The implementation of tahfidzul in UKM JQH UNISMA consists of the time of the activity, the place of the activity, and the method applied. 3) The results of tahfidzul tahfidzul at UKM JQH UNISMA are participants are able to complete memorization according to the level and quality of memorization that is followed, and participants are invited to represent the Musabaqah Hifdzil Qur'an (MHQ) competition at the MTQ (Musabaqah Tilawatil Qur'an) event at the university level . Regional, National, and International.